Nitrogen to protein conversion factors for the tropical spiny rock lobster (Panulirus ornatus), tiger prawn (Penaeus monodon), and brine shrimp (Artemia salina) - Adam Yeap; Basseer Codabaccus; David S. Nichols; Chris G. Carter (Aquaculture, 2027)

An Update on Advancement in Genomics Resources for Spiny Lobster Aquaculture Development - Courtney Lewis; Ahmad Farhadi; Susan Glendinning; Thomas Banks; Tara Kelly; Andrew G. Jeffs; Sandra Infante Villamil; John Breen; Jennifer M. Cobcroft; Arya Vazirzadeh; Basseer M. Codabaccus; Chris G. Carter; et al. (Reviews in Aquaculture, 2026)
The rapid advancement of high‐throughput sequencing technologies has transformed aquaculture genomics, enabling unprecedented insights into the biology and improvement of non‐model aquatic species. Among crustaceans, lobsters represent one of the most commercially valuable yet genomically underexplored taxa. This review synthesises the current state of genomic and transcriptomic resources available for spiny and slipper lobsters (Achelata), contextualising these within the broader decapod framework. We outline key genomic assemblies, transcriptomic atlases, and molecular tools that underpin emerging research on reproduction, nutrition, growth, stress tolerance, and disease resistance. We further highlight how omics‐driven approaches—spanning whole‐genome sequencing, SNP discovery, RNA interference, and nutrigenomics—are reshaping opportunities for selective breeding, reproductive control, and feed optimisation. Recent progress in establishing closed‐cycle aquaculture of Panulirus ornatus now provides the foundation for applying these molecular resources to address key production bottlenecks, including larval duration, cannibalism, and asynchronous moulting. We propose future directions integrating genomics, transcriptomics, and functional tools to accelerate sustainable domestication and genetic improvement of lobsters. Together, these advances mark a pivotal shift toward genomically informed spiny lobster aquaculture.

Preliminary studies of protein and energy requirements for hatchery-reared juvenile slipper lobster (Thenus australiensis) using a factorial model - Andrea Williamson; Chris G. Carter; M. Basseer Codabaccus; Quinn P. Fitzgibbon; Gregory G. Smith (Aquaculture International, 2026)
The slipper lobster ( Thenus australiensis ) is a promising aquaculture species, yet its nutritional requirements remain poorly defined compared to those of other crustaceans. A preliminary factorial model was developed in this study to quantify the daily protein and energy requirements of juvenile slipper lobsters, with demands partitioned into maintenance and growth components. Using data from two controlled growth experiments at 26 °C, regression analyses quantified weight gain as a function of body weight (g BW −1 day −1 ), feed intake, and whole-body composition across juveniles ranging from 5 to 83 g wet weight. Whole-body crude protein (CP) and gross energy (GE) content were stable across size classes, averaging 456 mg CP g BW −1 and 13 kJ GE g BW −1 on a dry-matter basis. Daily maintenance requirements were estimated at 10.8 mg digestible protein (DP) g BW −1 day −1 and 477 J digestible energy (DE) g BW −1 day −1 , with partial utilisation efficiencies of 0.45 for DP and 0.58 for DE. The model predicts shifting DP:DE ratios across instar stages, reflecting increasing maintenance costs with body size. These findings provide a foundation for defining the nutritional needs of juvenile slipper lobsters and deliver applied insights for feed formulation. By expressing requirements as absolute daily demands, the model offers a practical tool for hatchery and grow-out operations, supporting improved feed efficiency and reduced nutrient waste. The next step in validating and refining the model involves expanding research throughout the entire production cycle. Integrating new information and advances in nutritional needs and feed formulation will further enhance the model.

Crude protein requirements of tropical rock lobster (Palinurus ornatus Fabricius, 1798): A factorial model - Adam Yeap; Chris G. Carter; Basseer Codabaccus; Andrea Williamson; Quinn P. Fitzgibbon; Gregory G. Smith (Aquaculture, 2026)

Current and Future Approaches to Determining Amino Acid Requirements in Crustaceans - Adam Yeap; Chris G. Carter; Basseer Codabaccus; Quinn P. Fitzgibbon; Gregory G. Smith (Reviews in Aquaculture, 2026)
Nutrition is crucial in aquaculture, with feed ingredients and manufacturing being one of the largest expenditures. The effectiveness of a feed in promoting animal growth and health is dependent on ingredients with appropriate nutritional profiles. Proteins are a costly component of aquaculture feeds; moreover, dietary crude protein requirements for crustaceans can be high, sometimes exceeding 50% of the diet. As proteins are composed of amino acids, understanding species‐specific amino acid requirements is essential for developing cost‐effective, customised commercial feeds. Several methods have been used to determine crustacean amino acid requirements, each with advantages and limitations. Given the varied feeding behaviours between crustacean species, some methods may only be appropriate for certain species. In this review, we propose the Requirements by Ration Level approach as the most suitable method for developing factorial models for feed formulation. This method considers amino acid intake, retention, and loss, whilst integrating digestibility, growth, and chemical composition. It is reliable, accurate, and addresses concerns of amino acid balance changes previously raised in the literature. By using a broken convex curve model instead of a broken line model, more realistic predictions are produced, reflecting dynamic conditions and transitions towards the plateau where the amino acid requirement is met. Additionally, technological advancements have allowed complementary studies in omics, nutritional physiology, and true protein. This review highlights various methods for determining amino acid requirements and demonstrates how the Requirement by Ration Level approach can produce consistent results across experiments, reducing experimental repetition and advancing our understanding of amino acid requirements.

Thermal physiology of tropical rock lobster (Panulirus ornatus); defining physiological constraints to high temperature tolerance - Theodore Uy; Quinn P. Fitzgibbon; Basseer M. Codabaccus; Gregory G. Smith (Aquaculture, 2023)